Akseptabilitas Es Krim dengan Fortifikasi Mesocarp Lontar (Borassus flabeliffer L.) sebagai Antioksidan dan Serat Pangan Alami - Eny Idayati; Agrippina Agnes Bele; Rikka Welhelmina Sir (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Lontar palm (Borassus flabeliffer L.) fruit is one of the specific tropical fruits from East Nusa Tenggara province (NTT)-Indonesia that is rich in functional compounds such as beta-carotene as an antioxidant and food fiber. However, the utilization of these fruits is still limited due to the streroidal saponins and pholifenol content that makes them taste bitter and less favored by consumers. Therefore, one alternative that can be done is by enriching them into ice cream products. The production of Ice cream cannot go through with high heating processing so that the antioxidants extracted from lontar palm mesocarp can be in a stable condition. The aim of this study is to investigate the effect of ice cream on the acceptability values of the hedonic test, determining of fiber and beta-carotene content and evaluating antioxidant activities fortification from the lontar's mesocarp. The amount of lontar mesocarp for fortification (F) were 30%, 40% and 50% of the wet weight with the combination of some variation of milk treatment such as full cream milk, sweetened condensed milk, and liquid soy milk. The acceptability of the product was tested using hedonic test against color, aroma, texture, and flavor parameter. Antioxidant activity was performed by determination of the DPPH value (1.1-diphenyl-2picryhydrazil radical-scavenging), dietary fiber using enzymatic-gravimetric methods and UV-Vis spectrophotometers to analyze the content of beta-carotene. The results showed that on the acceptability test, the most preferred samples valued by panelists were the fortification, F1 treatment (30%) with the content of β-carotene of full cream milk was 2212.44 ± 11.82 μg /100 mg, dietary fiber was 8.95 ± 0.05%, and antioxidant activity was 45.54 ± 0.36%.